FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN NON KEUANGAN - Marvella Gabrielle Pratama; Jenny Vivianti (E-Jurnal Akuntansi TSM, 2022)
The objective of this research is to determine the factors that affect firm value. There 7 factors that used in this research, the factors are return on assets, debt to assets ratio, current ratio, firm size, dividend payout ratio, investment opportunity set, and total asset turn over on non financial companies that list on Indonesia Stock Exchange during periode 2018-2020. The samples are selected by using purposive sampling method and there are 96 companies that met the criteria and total 288 data. This research use multiple regression method for data analysis. The result of this research show that return on assets, debt to assets ratio, investment opportunity set have effect firm value. Meanwhile current ratio, firm size, dividend payout ratio, and total asset turn over have no effect on firm value.